(untitled) (Research, Society and Development, 2021)
This article has the purpose of describing suborder Heteroptera’s ecological aspects and associating them with some abiotic factors and environmental particulars. The gathering was made in six rivers, with a 50m transect divided among five 10m spots, where species were ghathered using an aquatic entomological D-net (rapiché), a sieve and manual scavenging on substrates incluinding leaves, trunks, macrophytes, roots, and others. Before the species gathering, it was obtained riparian vegetation data, bed types data, backwater and river áreas data, temperature data, pH data, electrical conductivity data, width data, depth data, velocity data, flow and canopy cover data. Besides, taxon richness data in the river were estimated by the non-parametric Jackknife richness test; for the physical and environmental parameters analysis, were used the Principal Coordinate Analysis and Redundancy Analysis; and the association between specimen was verified by the Bray-Curtis similarity matrix, after the data were transformed by log (x + 1). Were gathered 269 aquatic heteropterans, identified in two infraorders Gerromorpha and Nepomorpha with seven families and 17 genus. The most heterogeneous spots showed a higher richness of genus, although morphology and habitat specificity might influence their preference. The Jatobá river showed the greatest richness, with the analyses. This river had a better correlation with majority of genus, while the Baixa Grande Creek had a greater relation with most of the environmental variables and only a relation with the genus Pelocoris, and the genus which correlated with the substrate in a better way was Brachymetra. Richness and Ecology’s knowledging ascertains the ecosystems’ sensitivity and the living genus is required for conservation.